La scienza e i segreti della natura a Napoli nel Rinascimento La magia naturale di Giovan Battista Della Porta - Verardi, Donato (Premio Tesi di Dottorato, 2018)
This volume deals with the 'hidden secrets of nature' in the natural magic of Giovan Battista Della Porta (1535-1615). The topic is analysed in relation to the internal debates of the Neapolitan Aristotelianism of the 16th century and to the proposals of the magic tradition of the Renaissance. This book also deals with the problem of witchcraft, a phenomenon which is not purely philosophical, but connected historically to Della Porta's struggle against any form of superstitious explanation for natural secrets, including the roughest ones.